Persepsi Mahasiswa terhadap Pembelajaran Daring Berbasis Video dengan Bantuan Pen Tablet Selama Pandemi Covid-19 - Muhammad Reza; Rosi Hamama; Sulmia Maulida; Nurmalahayati Nurdin; Adean Mayasri; Noviza Rizkia (Orbital: Jurnal Pendidikan Kimia, 2021)
Online learning requires students to be more independent in learning. For example, chemistry learning tends to contain abstract concepts (very theoretical), so it requires a more detailed description and explanation. To help solve this problem, we need a media that can make it easier for students to learn during online learning. The purpose of this study was to determine student perceptions or responses to learning using teaching videos. The method used in this research is descriptive quantitative, which will produce a description of quantitative data related to student perceptions of the results of the Cronbach Alfa test. The instruments in this study were questionnaires, and learning outcomes test questions. The sample consisted of 102 students. Before being used, video-based learning media with the help of a pen tablet were validated by media and material experts, both in terms of construction and concepts contained in the learning media. The validation results obtained an average value of 0.91 which means it is very valid. Further analysis using reliability showed the Cronbach Alfa coefficients were 0.88, respectively; 0.92; 0.93 consecutively for aspects of knowledge, media and convenience. In order to be accepted by the media as learning media, it is necessary to look at student responses to aspects of knowledge (P) where the average value is 3.96 which is classified as good, media (M) 4.02 and convenience (K) 3.81 are also included in good category.